It’s Unexpected but Good: Leader Traditionality Fuels Greater Follower Reciprocation to Servant Leadership - Liao, Chenwei; Wu, Junfeng; Wayne, Sandy J.; Liden, Robert C.; Song, Lynda Jiwen (Journal of Management, 2025)
Integrating expectancy violation theory and social exchange theory, we investigate the role of leader traditionality in augmenting the positive effect of servant leadership in promoting follower reciprocation in three studies. In Study 1, we substantiate in an experiment that individuals indeed expect leaders possessing traditional values to be less likely to engage in servant leadership behaviors compared with leaders who are low in traditionality. Further, we test our full model in an experiment (Study 2) and find support for our hypothesis that the relationship between servant leadership, follower trust in the leader, and subsequent follower organizational citizenship behavior is stronger for leaders higher (vs. lower) in traditional values. Replicating the findings from Study 2, we conduct a field investigation (Study 3) with multiwave and multisource data from a Fortune 500 company and obtain full support for our model. The consistent findings across our studies provide strong support for the role of leader traditionality in altering the social exchange relationship between servant leaders and their followers.